Density of Trichospilus diatraeae (Hymenoptera: Eulophidae) Parasitizing Diaphania hyalinata (Lepidoptera: Crambidae) Pupae - Silva, Isabel M.; Zanuncio, Teresinha V.; Pereira, Jose M. M.; Wilcken, Carlos Frederico [UNESP]; Pereira, Fabricio F.; Serrao, Jose E.; Zanuncio, Jose C. (Entomological Soc Amer, 2014)
Diaphania hyalinata L. (Lepidoptera: Crambidae) is a key pest of plants in the family Cucurbitaceae, defoliating and reducing photosynthetic area and yield. Trichospilus diatraeae Margabandhu & Cherian, 1942 (Hymenoptera: Eulophidae) parasitizes the pupae of this pest, but its biological and reproductive parameters with this host are unknown. The objective of our study was to characterize the reproduction of T. diatraeae in D. hyalinata pupae with different densities of this parasitoid. Individual D. hyalinata pupae (48 h old) were exposed to different densities of T. diatraeae (1:1, 4:1, 8:1, 12:1, 16:1, 20:1, and 24:1). The parasitoid density did not affect the parasitism and emergence rate of this natural enemy. The progeny, sex ratio, longevity, and head capsule width of T. diatraeae males and females decreased with increasing density, and its life cycle was proportional to density increase of T. diatraeae. Densities of up to eight T. diatraeae individuals per D. hyalinata pupae are favorable for the development of this parasitoid.
Keywords: density; Eulophidae; parasitism; mass rearing